A SOCIOLINGUISTIC STUDY OF THE USE OF ENGLISH TABOO TERMS IN MIKE LACHER’S ON THE BRO’D - Raihna Meiska Pasaribu; Obat Mikael Depari; Yuli Widiana (Humaniora Scientia, 2017)
This research focuses on taboo terms found in Mike Lacher’s On the Bro’d. Theaims of this research are to describe the kinds of taboo terms and their usage. Thisresearch uses descriptive method which involves the following steps: collecting,classifying, and analyzing the data. Library research is used as technique of datacollecting. The population of this research is all of the terms and phrasescontaining taboo terms. The data of the research are analyzed one by one,therefore, the total sampling is applied. Referential equivalent method is used todetermine the kinds of taboo terms. Meanwhile, pragmatic equivalent method isused to analyze the purpose of using taboo terms. Due to the kinds of taboo termsfound in the novel, the taboo terms include religion taboo terms, disease, deathand killing, bodily excretion taboo terms, personal name, sexual organ, sexualactivity, gender identity, and mental illness. The mostly used taboo term in thenovel is sexual taboo term while the least is disease, death and killing. In terms ofthe purposes of their usage taboo terms are used to express anger, surprise, curseor wish harm, habitual epithets, insult, joke or humor, sex talk, and slang. Amongthem, insult is the most intended purpose which occurs in the novel; whereas,slang is the least.